Oxidative esterification of methylarenes and 1, 3‐dicarbonyls catalysed by copper chloride immobilized on magnetic nanoparticles. (25th November 2016) - Nakisa, Athar; Karimi, Meghdad; Yazdani, Elahe; Heydari, Akbar
Abstract : Superparamagnetic CuCl nanoparticles were prepared and identified as an effective heterogeneous catalyst for the tandem transformation of methylarenes and 1, 3‐dicarbonyl compounds into the corresponding enole esters by the use of tert ‐butyl hydroperoxide as an external oxidant. The catalyst can be removed from the reaction medium simply by use of an external magnet. As a consequence, various derivatives of enol esters were synthesized in moderate to good yields. Abstract : Methylarenes are used as simple, inexpensive and available precursors for the synthesis of enolesters. Supported metal by ionic liquid are designed as an efficient, inexpensive, recoverable easy handeled heterogeneous catalyst. TBHP is applied as a green and temperate oxidant.